The Effect of Complementary Hydrotherapy Using Warm Water on Blood Pressure Reduction in Hypertensive Pregnant Women at a Health Center in Palu City - Chen, Asriwidyayanti; Silfia, Niluh Nita; Putri, Winda Inayah (Poltekkes Kemenkes Palu, 2025)
Background: Hypertension in pregnancy remains one of the leading causes of serious complications that increase maternal morbidity and mortality, thus requiring safe and simple non-pharmacological interventions. This study aims to determine the effect of hydrotherapy using warm water on reducing blood pressure in pregnant women with hypertension. Method: This study employed a pre-experimental study with a one-group pretest–posttest design was conducted involving 30 purposively selected pregnant women with hypertension. The intervention consisted of foot immersion in warm water at 40 °C for 30 minutes, performed twice within two weeks. Blood pressure was measured before and after the intervention and analyzed using the Wilcoxon signed-rank test. Result: The intervention showed a significant reduction in systolic blood pressure, with an average decrease of 14 mmHg, and in diastolic blood pressure, with an average decrease of 10 mmHg (p < 0.001). Conclusion: Warm water hydrotherapy is effective in lowering blood pressure in pregnant women with hypertension. It is recommended that this therapy be adopted by healthcare providers as a non-pharmacological option and promoted for self-practice among pregnant women to help prevent pregnancy complications